Chloride Content of Fluids Used for Large-Volume Resuscitation Is Associated With Reduced Survival. Issue 2 (February 2017) - Sen, Ayan; Keener, Christopher M.; Sileanu, Florentina E.; Foldes, Emily; Clermont, Gilles; Murugan, Raghavan; Kellum, John A.
Abstract : Objective: We sought to investigate if the chloride content of fluids used in resuscitation was associated with short- and long-term outcomes. Design: We identified patients who received large-volume fluid resuscitation, defined as greater than 60 mL/kg over a 24-hour period. Chloride load was determined for each patient based on the chloride ion concentration of the fluids they received during large-volume fluid resuscitation multiplied by the volume of fluids. We compared the development of hyperchloremic acidosis, acute kidney injury, and survival among those with higher and lower chloride loads. Setting: University Medical Center. Patients: Patients admitted to ICUs from 2000 to 2008. Interventions: None. Measurements and Main Results: Among 4, 710 patients receiving large-volume fluid resuscitation, hyperchloremic acidosis was documented in 523 (11%). Crude rates of hyperchloremic acidosis, acute kidney injury, and hospital mortality all increased significantly as chloride load increased ( p < 0.001). However, chloride load was no longer associated with hyperchloremic acidosis or acute kidney injury after controlling for total fluids, age, and baseline severity. Conversely, each 100 mEq increase in chloride load was associated with a 5.5% increase in the hazard of death even after controlling for total fluid volume, age, and severity ( p = 0.0015) over 1 year. Conclusions: Chloride load is associated with significant adverse effects on survival out to 1 year even after controlling for total fluid load, age, and baseline severity of illness. However, the relationship between chloride load and development of hyperchloremic acidosis or acute kidney injury is less clear, and further research is needed to elucidate the mechanisms underlying the adverse effects of chloride load on survival. Abstract : Supplemental Digital Content is available in the text.